Optimization of reaction conditions for the production of cyclodextrin (CD) using cyclodextrin glucanotransferase (CGTase) immobilized on hollow fiber membrane - S., Suhaimi; Rohaida, Che Man; Natassha, Jamil; Zatul Iffah, Mohd Arshad; Shalyda, Md Shaarani; Siti Kholijah, Abdul Mudalip; Siti Zubaidah, Sulaiman (IOP Publishing, 2020)
Cyclodextrin glucanotransferase (CGTase) is an enzyme that convert starch into cyclodextrin (CD) by transglycosylation reaction. The CD has been used in various industries due to the unique characteristics. However, the production of CD is usually restricted due to the instability of the enzyme which easily denatured during the reaction process. Thus, enzyme immobilization technique was applied and optimization of reaction conditions was conducted to enhance the amount of CD production. In this study, CGTase was immobilized on polyvinylidiene difluoride (PVDF) hollow fiber membrane by adsorption. The optimization of the reaction conditions using response surface methodology (RSM) on the production of CD was studied. Under optimized conditions (2.8% w/v of soluble potato starch concentration, 45.2°C of reaction temperature and pH 5.6), the production of CD was 5.65 mg/mL, about 2-fold compared to the value before optimization process. Therefore, the immobilized CGTase on hollow fiber membrane proved to be valuable for the enhancement of CD production.